2019
DOI: 10.1016/j.chiabu.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substantiated and unsubstantiated investigations of child maltreatment and subsequent adolescent health

Abstract: Children with substantiated child maltreatment (CM) experience adverse health outcomes. However, it is unclear whether substantiation vs. an investigation not resulting in substantiation has a greater impact on subsequent adolescent health. Propensity scores were used to examine the effect of investigated reports on the subsequent health of 503 adolescent females. CM was categorized into three levels: 1) investigated and substantiated, 2) investigated but unsubstantiated, and 3) no investigation. Models using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…However, the CTQ is a widely used instrument and examinations of the effects of child maltreatment experiences outside of the scope of expensive, longterm prospective studies are bound to suffer from assessment challenges as many cases of child maltreatment go unreported even in official records. Somewhat encouragingly, retrospective self-reports may include more false negative than false positive reports, suggesting that associations reported here may be conservative (46). Relatedly, participants in this study were generally healthy and reported overall low to moderate levels of child maltreatment experiences which may explain the absence of hypothesized associations between sexual and physical abuse history and acute inflammatory stress reactivity.…”
Section: Discussionmentioning
confidence: 59%
“…However, the CTQ is a widely used instrument and examinations of the effects of child maltreatment experiences outside of the scope of expensive, longterm prospective studies are bound to suffer from assessment challenges as many cases of child maltreatment go unreported even in official records. Somewhat encouragingly, retrospective self-reports may include more false negative than false positive reports, suggesting that associations reported here may be conservative (46). Relatedly, participants in this study were generally healthy and reported overall low to moderate levels of child maltreatment experiences which may explain the absence of hypothesized associations between sexual and physical abuse history and acute inflammatory stress reactivity.…”
Section: Discussionmentioning
confidence: 59%
“…Finally, it is important to acknowledge that 20% of current sample included children with unsubstantiated investigations of CM, which some suggest may confer a different level of risk compared to those with substantiated reports. However, prior work has shown a degree of equivalency between those with and without substantiated CM reports in terms of the risk of adverse/maladaptive long-term outcomes (Kohl, Jonson-Reid, & Drake, 2009;Kugler et al, 2019;Leiter, Myers, & Zingraff, 1994), suggesting a level of similarity in the experiences of those whose cases are investigated but not substantiated and those that are substantiated.…”
Section: Discussionmentioning
confidence: 98%
“…Although the sample included children with substantiated and unsubstantiated reports of CM, there is long-standing evidence that the physical and psychological consequences of CM do not differ for substantiated and unsubstantiated reports (Kohl, Jonson-Reid, & Drake, 2009;Kugler et al, 2019;Leiter, Myers, & Zingraff, 1994).…”
Section: Participantsmentioning
confidence: 99%
“…Nevertheless, the information substantiated in child protection records may be that one most easily proved by social workers, rather than a full account of the children's lived experience. For example, previous research has shown that substantiated and unsubstantiated cases for maltreatment in child protection services do not differentiate with regard to later health outcomes or risk for later reports of maltreatment (Kohl, Jonson‐Reid, & Drake, 2009; Kugler et al, 2019). Therefore, some information relevant for understanding the children's maltreatment experiences may have been missing.…”
Section: Discussionmentioning
confidence: 99%